EVALUASI KEBIJAKAN PUBLIK UNIVERSITAS NEGERI (PTN) TERKAIT KEBIJAKAN KENAIKAN BIAYA KULIAH - Rindi Astika Yuliana; Istiana Hermawati (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2024)
Education is one of the fields that is quite important and strategic in a state system. Good education will be able to produce good community resources as well. In its journey, education will determine the future of a nation. The compulsory education program which has been widely promoted in every corner of the country is a manifestation of the government's attention to building good and decent education for the community. Decent education must be compatible with existing societal conditions. The government must not ignore this. One of the things that is in the spotlight is how to be able to accommodate educational needs by providing compulsory education that is affordable in terms of costs, even if possible, all forms of education are borne by the government because in reality the government must be able to guarantee the intelligence of a nation. Education in Indonesia so far only guarantees continuity for 12 years. In fact, the public's desire to deepen their knowledge further should also be the government's concern. Even though the government cannot fully accommodate the financing of further education processes such as at universities and so on, at least the government is able to provide relief and a way out for the nation's next generation who want to deepen and expand their knowledge. Regulation of the Minister of Education, Culture, Research and Technology of the Republic of Indonesia Number 2 of 2024 concerning Unit Standards for Higher Education Operational Costs at State Universities within the Ministry of Education has generated a lot of controversy, and this regulation has even led to many demonstrations at several State Universities in Indonesia. Minister of Education and Culture Regulation No. 2 of 2024 concerning UKT regulations is currently being hotly discussed, because these regulations have caused tuition fees at a number of PTN to soar. Following this, quite a few are curious about how to calculate UKT based on parents' salaries. Minister of Education and Culture Regulation No. 2 of 2024 contains regulations for increasing UKT for new students. The increase will not apply to existing students who have studied at PTN. Several PTN affected by the UKT increase include the University of Indonesia (UI) campus. Jenderal Soedirman University (Unsoed), Brawijaya University (UB), UIN Syarif Hidayatullah, Sebelas Maret University (UNS), Yogyakarta State University (UNY) and Sepuluh Nopember Institute of Technology (ITS). Even though in the end the Ministry of Education and Culture postponed the discourse, disappointment from the community, especially parents who were studying their children at PTN, felt frustrated because they were unable to pay for UKT.